Osthole inhibits gastric cancer cell proliferation through regulation of PI3K/AKT - Xu, Xiaojun; Liu, Xiaoyuan; Zhang, Yan (PLOS ONE, 2018)
Osthole is an active compound isolated from Chinese herb Cnidium monnieri (L.) Cusson, and had been reported to possess antitumor effect. However, the effect of osthole on the gastric cancer cells has not been investigated. In this study, the effects of osthole on the proliferation of human gastric cancer cells were tested. The data showed that osthole treatment significantly inhibited the proliferation of gastric cancer cells and resulted in the cell cycle arrest at G2/M phase in a dose-dependent manner. Western-blot study showed that the expression of cyclin B1 and cdc2 was markedly reduced by osthole. Moreover, expression of PI3K and pAKT was also significantly suppressed, and the results indicated that the inhibition of pAKT, cyclin B1, and cdc2 levels by osthole was notably enhanced by a PI3K inhibitor. These results demonstrate that osthole could inhibit gastric cancer cells proliferation via induction of cell cycle arrest at G2/M phase by the reduction of PI3K/AKT.